Nematodiasis in laying ducks (Anas platyrhynchos) at different age groups - Khasanah , Intania N.; Widiyono , Irkham (Fakultas Peternakan Universitas Papua, 2025)
Nematodiasis remains a critical parasitic disease affecting the gastrointestinal health and productivity of laying ducks. This study aimed to investigate the occurrence of nematode infections at different ages in laying ducks (Anas platyrhynchos). A total of 100 intensively managed local ducks were used, comprising 50 young ducks (2.5–5 months) and 50 adults (7 months–1 year). Fecal samples were analyzed using the modified Whitlock flotation technique. Descriptive analysis and Chi-square statistical testing were performed using SPSS software. The overall occurrence of nematodiasis was 37% (37/100), with Capillaria sp. being the most frequently detected species (24%), followed by Strongyloides sp. (19%) and Ascaridia sp. (1%). Single-species infections predominated (81.1%), while mixed-species infections accounted for 18.9% of positive cases. Eggs per gram (EPG) values varied among age groups but were consistently within the mild infection range. Statistical analysis revealed a significant association between age group and infection occurrence (p<0,05), indicating that younger ducks are at higher risk of nematode infection. These findings highlight the importance of age-specific parasite control strategies to enhance flock health and productivity in laying duck operations.